MicroRNAs in the thyroid - Boufraqech, Myriem (Best Pract Res Clin Endocrinol Metab, 2016)
The microRNAs (miRNAs) are small non-coding RNA comprising approximately 19–25 nucleotides. miRNAs can act as tumour suppressors or oncogenes, and aberrant expression of miRNAs has been reported in several human cancers and has been associated with cancer initiation and progression. Recent evidence suggests that miRNAs play a major role in thyroid carcinogenesis. In this review, we summarize the role of miRNAs in thyroid cancer and describe the oncogenic or tumour suppressor function of miRNAs as well as their clinical utility as prognostic or diagnostic markers in thyroid cancer.